Prevalence and normative values for jaw functional limitations in the general population in Sweden - Oghli, Ibrahim; List, Thomas; John, Mike T.; Häggman‐Henrikson, Birgitta; Larsson, Pernilla (Oral diseases, 2019)
Objectives For jaw functional limitations measured by the Jaw Functional Limitation Scale (JFLS), (a) determining prevalence in the Swedish general adult population, (b) investigating the influence of demographic factors and self‐reported dental status and (c) deriving normative values. Methods A random sample of the general adult population in Sweden was approached (response rate: 46%, N = 1,372). Prevalence was determined for the JFLS summary score and individual items. The influence of age, gender and dental status was investigated with regression analyses and normative values presented. Results The JFLS median score was 0, and all items had prevalences ≤30%. Age and gender did not influence jaw functional limitations but dental status did. Normative JFLS scores were 1, 9 and 28 for the 7th, 8th and 9th deciles, respectively. In dental status‐stratified norms, 9th deciles were 20, 43 and 100, for subjects with natural teeth only, removable and complete dentures, respectively. Conclusions The Swedish general adult population had excellent jaw function, but dental status was major determinant. In the absence of information linking JFLS scores to important patient concerns, the score distribution can serve as a reference with the 9th decile as threshold for functional limitation.